Aspects of speech-language abilities are influenced by MECP2 mutation type in girls with Rett syndrome - Urbanowicz, A.; Downs, Jennepher; Girdler, S.; Ciccone, N.; Leonard, H. (2015)
This study investigates relationships between methyl-CpG-binding protein 2 gene (MECP2) mutation type and speech-language abilities in girls with Rett syndrome. Cross-sectional data on 766 girls, aged 15 years and under, with genetically confirmed Rett syndrome was obtained from the Australian Rett Syndrome Database (ARSD) (n=244) and the International Rett Syndrome Phenotype Database (InterRett) (n=522). Relationships between MECP2 mutation type and age of regression in speech-language abilities, and the level of speech-language abilities before and after this regression were investigated. The females had a median age of 4.95 years in the ARSD and 5.25 years in InterRett. The majority (89%, 685/766) acquired speech-language abilities in the form of babble or words at some point in time. Of those who acquired babble or words, 85% (581/685) experienced a regression in these abilities. Those with a p.Arg133Cys mutation were the most likely to use one or more words, prior to (RRR=3.45; 95% CI 1.15-10.41) and after (RRR=5.99; 95% CI 2.00-17.92), speech-language regression. Girls with Rett syndrome vary in their use of speech and language, and in their experience of speech-language regression and these variations are partly explained by genotype.